Synthesis of high-voltage cathode material using the Taylor-Couette flow-based co-precipitation method - Lee, Junghwan; Song, Young-Woong; Lee, HyoChan; Kim, Min-Young; Lim, Jinsub (Frontiers in Chemistry, 2023)
LiNi0.5Mn1.5O4 (LNMO), a next-generation high-voltage battery material, is promising for high-energy-density and power-density lithium-ion secondary batteries. However, rapid capacity degradation occurs due to problems such as the elution of transition metals and the generation of structural distortion during cycling. Herein, a new LNMO material was synthesized using the Taylor Couette flow-based co-precipitation method. The synthesized LNMO material consisted of secondary particles composed of primary particles with an octahedral structure and a high specific surface area. In addition, the LNMO cathode material showed less structural distortion and cation mixing as well as a high cyclability and rate performance compared with commercially available materials